High-performance electromagnetic shielding material with flame retardancy and preparation method thereof
Through the self -assembly and functional polymer base of the MXENE and epoxy cage type, the covalent -linked network of the base price of the polymer base, the problems of the processed and electromagnetic shielding performance of the existing flexible electromagnetic shielding materials have been solved. The preparation of performance electromagnetic shielding materials has excellent friction, anti -fatigue and flame retardant performance.
Patent Information
- Application Number
- CN202310214537.7
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2023-03-08
- Publication Date
- 2025-01-28
- Estimated Expiration
- 2043-03-08
AI Technical Summary
The existing flexible electromagnetic shielding materials have shortcomings in terms of processability and electromagnetic shielding performance, and MXene has poor compatibility when compounded with polymer materials, resulting in the conductive network being easily destroyed and the flame retardant performance needs to be further improved.
The aqueous solution and epoxy cage type double silicoxane self -assembly with MXENE nanosiline sheet to form a spray solution, sprayed to the functional polymer base of pre -stretching, and form an electromagnetic shield film under heating conditions. Improve friction resistance and fatigue performance, and use the flame retardant performance of EPOSS to improve the flame retardant performance.
The preparation of high -performance electromagnetic shielding materials has been realized, and it has excellent friction, anti -fatigue and flame retardant performance. The electromagnetic shielding efficiency is high, the cost is low, and the operation is simple.
Smart Images

Figure CN116199925B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to an electromagnetic shielding material, in particular to a flame retardant high-performance electromagnetic shielding material and a preparation method thereof. Background Art
[0002] With the development of 5G wireless communication technology and artificial intelligence, the functions of testing, data collection, data storage, etc. carried by precision electronic equipment in automobiles, aircraft, etc. are gradually being applied. Precision electronic equipment will be affected by external electromagnetic interference during use, resulting in electronic equipment failure and information leakage. Therefore, damping materials with electromagnetic shielding performance play an important role in ensuring the stable operation of precision electronic equipment and information confidentiality. Flexible electromagnetic shielding materials with deformable ability have the characteristics of light weight, good flexibility and good processing performance, and are widely studied in the field of electromagnetic shielding. Flexible electromagnetic shielding materials are mainly prepared by compounding polymer materials with conductive materials such as metals, carbon materials, and conductive polymers. The existing technology has the disadvantages of high conductive filler filling, poor processing performance, and poor electromagnetic shielding performance.
[0003] MXene is a family of two-dimensional (2D) transition metal carbides and / or nitrides reported in 2011. It has excellent metallic conductivity but a density far less than that of metal materials, and is very promising in the fields of electromagnetic interference (EMI) shielding and wave absorption. 3 C 2 T x The cost is relatively low and the preparation method is relatively simple, making it the most widely studied type of MXene in EMI shielding applications. 3 C 2 T x The conductivity of the membrane reached 4665S cm -1 , EMI shielding efficiency (SE) is 92dB (8.2~12.4GHz, X-band), which is similar to that of metal materials. In addition, the surface of MXene contains -O, -F, -OH functional groups, and the nanosheets have very good hydrophilicity and can be suspended in water as a single layer of nanosheets. However, when compounded with polymer materials, there is a problem of poor compatibility, which leads to the stacking of nanosheets and the inability to exert its excellent conductive advantages. Special processes are required to maximize its advantages.
[0004] Chinese patent CN 111592684 A discloses a thermoplastic elastomer composite Ti 3 C 2 T xA method for preparing an electromagnetic shielding material, in which a low-filling, high-electromagnetic shielding effect electromagnetic shielding material is obtained by immersing microporous foamed thermoplastic elastomer beads into an aqueous dispersion of MXene. However, a large amount of formic acid is required to dissolve the surface of the microporous beads during the preparation process, and the formic acid is subsequently removed by alkali washing and water washing. This process is environmentally unfriendly and easily damages the MXene conductive layer. Chinese patent CN 110117331 A discloses a method for preparing a MXene-based electromagnetic shielding coating material, in which a MXene aqueous dispersion is modified by dopamine and blended with a polypyrrole bead dispersion wrapped in polyvinyl alcohol, which can be applied to the surface of the base material to form an electromagnetic shielding coating. In this method, there is no covalent bond between MXene and polyvinyl alcohol, the interaction is weak, and the conductive network is easily destroyed.
[0005] The aqueous dispersion of MXene is electronegative and can self-assemble with positively charged nano-ions in water to form a stable dispersion of 2D sheets, which makes large-area spraying possible. However, the concentration of the aqueous dispersion of MXene is very low, and a large amount of spraying liquid is required to spray repeatedly to obtain an effective conductive coating. In addition, the sliding between the stacked MXene sheets leads to poor deformation resistance of the coating, and the poor adhesion of the film makes it easy to fall off from the substrate.
[0006] In addition, electronic products generate a lot of heat during use, and the risk of fire is high. In recent years, MXene has been proven to reduce the amount of smoke generated by polymer materials during combustion through the tortuous path effect of nanosheets, and MXene has a high thermal conductivity, which can reduce heat accumulation and reduce the risk of fire. It is a very promising flame-retardant nanomaterial. However, MXene performs poorly in reducing burning time, and its thermal conductivity also makes it easy to transfer heat from external fire sources, making the material more easily ignited. Its flame retardant properties need to be further improved for application in the flame retardant direction. Summary of the invention
[0007] The purpose of the present invention is to provide a high-performance electromagnetic shielding material with flame retardancy. The stretch spray method and the covalent cross-linking network make it have excellent friction resistance and fatigue resistance. The cage Si-O structure of epoxy cage silsesquioxane (EPOSS) makes it have excellent flame retardancy. In addition, the chemically modified 1,2-PB has good adhesion to the material and contains residual double bonds that can further react. It can be coated on a variety of materials and has broad application prospects.
[0008] The invention also provides a preparation method thereof, which is scientific, reasonable, simple and easy to implement.
[0009] The technical solution adopted by the present invention is specifically as follows:
[0010] The method for preparing the flame-retardant high-performance electromagnetic shielding material uses a dispersion formed by self-assembly of an aqueous solution of MXene nanosheets and epoxy cage-shaped silsesquioxane as a spraying liquid, which is sprayed onto a pre-stretched functionalized polymer substrate to form an electromagnetic shielding film under heating conditions.
[0011] Specifically, the method for preparing the flame retardant high-performance electromagnetic shielding material adopts an active-stretching spraying strategy, namely, Ti 3 C 2 T x The dispersion formed by self-assembly of an aqueous solution of type MXene and epoxy cage-shaped silsesquioxane under alkaline conditions is used as a spraying liquid, which is sprayed onto a functionalized 1,2-polybutadiene substrate under pre-stretching conditions, and a covalent bond is formed between the coating and the substrate under heating conditions to form an electromagnetic shielding film.
[0012] The MXene nanosheet is a single / few-layer Ti 3 C 2 T x Nanosheets, MXene nanosheets and epoxy cage-shaped silsesquioxane have a mass ratio of 100:5 to 15, and they are self-assembled into a spray liquid with reactive groups under electrostatic interaction.
[0013] Preferably, Ti 3 C 2 T x Type MXene nanosheets are made of Ti 3 AlC 2 The obtained product is etched by a mixed aqueous solution of LiF and HCl. After the above etching solution is rinsed and filtered to neutrality, deionized water is added. Water: Ti 3 AlC 2 =400:1 (mass ratio), ultrasonicated at 0-5°C for 1 hour, and then centrifuged at 3500 rpm for 3 min in a centrifuge to remove the unpeeled MXene and obtain single / multilayer Ti 3 C 2 T x Aqueous dispersion, wherein Ti 3 C 2 T x The concentration is 1 mg / mL.
[0014] The aqueous solution of the MXene nanosheets is adjusted to a pH of 8 to 10 by triethylamine, preferably to a pH of 8 to 9.
[0015] The dispersion formed by self-assembly of the aqueous solution of the MXene nanosheets and epoxy cage-shaped silsesquioxane is prepared by dissolving the epoxy cage-shaped silsesquioxane in a polar organic solvent and then adding the solvent to the aqueous solution of the MXene nanosheets, and mixing the mixture uniformly by stirring or ultrasonic treatment; preferably, the polar organic solvent is tetrahydrofuran.
[0016] The functionalized polymer substrate is 1,2-polybutadiene functionalized with hydroxyl, carboxyl or amino groups, and the grafting rate is 40-70%.
[0017] The hydroxyl, carboxyl or amino functionalized 1,2-polybutadiene is prepared by a click chemistry method using 1,2-polybutadiene and a thiol containing a hydroxyl, carboxyl or amino group. The preparation steps include: dissolving 1,2-polybutadiene rubber in a polar organic solvent, adding the thiol, adding a photoinitiator, and initiating the reaction by ultraviolet light at room temperature (20-40)°C for 4-10 minutes; the amount of the photoinitiator used is 0.4-1% of the mass of the 1,2-polybutadiene rubber.
[0018] The thiol containing hydroxyl, carboxyl or amino group is at least one of 3-mercaptopropionic acid, 2-mercaptoethanol, mercaptoethylamine and cysteine, and the added amount is 0.2-1:1 (thiol: butadiene, molar ratio).
[0019] The number average molecular weight of the 1,2-polybutadiene is 1000-150000, and the 1,2-structure content is 75-95%.
[0020] The heating condition is heating at 140-160° C. for 20-40 minutes.
[0021] The high-performance electromagnetic shielding material with flame retardancy provided by the present invention is prepared by adopting the above-mentioned preparation method.
[0022] Compared with the prior art, the present invention has the following beneficial effects:
[0023] 1.MXene nanosheets and negatively charged epoxy cage silsesquioxane can form a spray liquid through electrostatic self-assembly in water. Epoxy cage silsesquioxane reduces the surface energy of MXene. After spraying onto the functionalized polymer substrate, the MXene nanosheets are more stretched on the substrate, and the constructed conductive network has high conductivity. Only 3 to 5 g of MXene per square meter is needed to prepare an electromagnetic shielding network with an electromagnetic shielding efficiency of 27 dB (commercial requirements are greater than 20 dB), which is low cost and simple to operate.
[0024] 2. The functionalized polymer substrate used is 1,2-polybutadiene modified by click chemistry. The grafting rate is adjustable in a wide range and the surface energy is high, which can make MXene nanosheets better dispersed. In addition, the functionalized polymer substrate has good adhesion to metal materials and rubber materials and can be used in a variety of occasions.
[0025] 3. Epoxy cage silsesquioxane has Si-O bonds, which cover the polymer surface after spraying, and play a barrier role while retaining most of the thermal conductivity of MXene, so that the electromagnetic shielding material has a long ignition time (TTI), extinguishes quickly, produces less smoke, and has improved flame retardant properties.
[0026] 4. The epoxy groups on the epoxy cage silsesquioxane react with the hydroxyl groups on the MXene and the functional groups on the functional polymer to form covalent bonds. The MXene sheets are not easy to fall off. Combined with the pre-stretching spraying strategy, the prepared electromagnetic shielding material has excellent friction resistance and fatigue resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0027] Figure 1 Ti 3 C 2 T x SEM images of nanosheets, a is the Al layer after etching, showing an accordion shape, b is the Ti layer after ultrasonication 3 C 2 T x The nanosheets are opened and dispersed as single / multiple sheets;
[0028] Figure 2 : a is the obtained sample picture, b is the thickness of the conductive coating on the surface of the sample, which is about 2 μm, and c is the electromagnetic shielding performance of the samples of Comparative Example 1 and Example 2;
[0029] Figure 3 Electron microscope photos of the surfaces of Comparative Example 1 (a) and Example 3 (b) after being treated with sandpaper;
[0030] Figure 4 The resistance changes after bending fatigue of Comparative Example 2 and Example 4 are shown. DETAILED DESCRIPTION
[0031] In order to make the above-mentioned purpose, features and advantages of the present invention more obvious and easy to understand, the specific embodiments of the present invention are described in detail below. In the following description, many specific details are set forth to facilitate a full understanding of the present invention. However, the present invention can be implemented in many other ways different from those described herein, and those skilled in the art can make similar improvements without violating the connotation of the present invention, so the present invention is not limited by the specific embodiments disclosed below.
[0032] Unless otherwise defined, all technical and scientific terms used herein have the same meaning as those commonly understood by those skilled in the art of the present invention. The terms used in the specification of the present invention herein are only for the purpose of describing specific embodiments and are not intended to limit the present invention.
[0033] All raw materials of the present invention have no particular restrictions on their sources, and can be purchased from the market or prepared according to conventional methods known to those skilled in the art. The water used in the present invention is deionized water; the test methods of "sample preparation and treatment" involved in the present invention are conventional methods unless otherwise specified.
[0034] Comparative Example 1
[0035] In a polytetrafluoroethylene flask, add 4g LiF, then add 50mL 8mol / L HCl, stir evenly with magnetic force, and slowly pour in 2.5g Ti 3 AlC 2 , react at 45 ° C for 48 h, filter and rinse with deionized water until the pH is neutral to obtain Ti 3 C 2 T x Add 1000 mL of deionized water and place in an ice water bath at 0-5°C for 60 minutes to make Ti 3 C 2 T x The nanosheets were peeled off and centrifuged at 3500 rpm for 3 min to remove the unpeeled Ti 3 C 2 T x Nanosheets, single / multilayer Ti 3 C 2 T x Aqueous dispersion, referred to as T5. Figure 1 As shown, a is the Ti after etching 3 C 2 T x Nanosheets, the Al layer is etched away, showing an accordion shape, b is after ultrasonic treatment, Ti 3 C 2 T x The nanosheets were opened and dispersed in aqueous solution in single / multilayer forms.
[0036] Under constant nitrogen conditions, 0.54g of 1,2-PB with a number average molecular weight of 100,000 and a 1,2-structure content of 80% was dissolved in 20mL of tetrahydrofuran, 0.5mL of 3-mercaptopropionic acid (SH: butadiene = 0.5:1, SH is mercapto, Bd is butadiene, molar ratio) was added to the solution and stirred evenly, and then 15mg (0.6wt%) of photoinitiator dimethyl benzoate (DMPA) was dissolved in 1mL of tetrahydrofuran and added to the solution. The reaction was placed under a 365nm ultraviolet lamp for 6min. After the reaction was completed, 1mL of ethanol containing 1wt% 264-antiaging agent was added to the system to terminate the reaction. The product was poured into a mold and dried to obtain 1,2-polybutadiene with a carboxyl grafting rate of 50%, referred to as CPB50.
[0037] When CPB50 is pre-stretched 100%, T5 is sprayed onto the surface of CPB using a spray gun, both sides are sprayed, and the material is heated at 150° C. for 30 minutes to obtain a polymer material with a conductive coating, referred to as CPB50-T5.
[0038] Example 1
[0039] The obtained 1000mL Ti with a concentration of 1mg / mL 3 C 2 T x The pH of the aqueous dispersion was adjusted to 8 with triethylamine, and 50 mg of EPOSS was added and stirred at room temperature for 24 hours to obtain an active spray solution, referred to as AS5.
[0040] The preparation method of CPB is the same as that of Comparative Example 1, except that SH:butadiene=0.2:1, the amount of DMPA used is 10 mg (0.4 wt%), the illumination time is 4 min, and the carboxyl grafting rate is 40%, referred to as CPB40.
[0041] The spraying method is the same as that of Comparative Example 1, except that the spraying liquid is AS5 and the obtained material is CPB40-AS5.
[0042] Example 2
[0043] The obtained 1000mL Ti with a concentration of 1mg / mL 3 C 2 T x The pH of the aqueous dispersion was adjusted to 9 with triethylamine, and then 100 mg of EPOSS was added and stirred at room temperature for 24 hours to obtain an active spray solution, referred to as AS10.
[0044] The preparation method of CPB is the same as that of Comparative Example 1, except that SH:butadiene=0.5:1, the amount of DMPA used is 10 mg (0.6 wt%), the illumination time is 6 min, and the carboxyl grafting rate is 50%, referred to as CPB50.
[0045] The spraying method is the same as that of Comparative Example 1, except that the spraying liquid is AS10 and the obtained material is CPB50-AS10.
[0046] Figure 2 a is the sample image obtained, Figure 2 b is the thickness of the conductive coating on the sample surface, which is about 2 μm. Figure 2 c is the electromagnetic shielding performance of the samples of comparative example 1 and example 2. The electromagnetic shielding efficiency (SE) of example 2 is significantly improved, and the SE values are all higher than 20 dB at 5000-12500 MHz, which meets commercial requirements.
[0047] Example 3
[0048] The obtained 1000mL Ti with a concentration of 1mg / mL 3 C 2 T x The pH of the aqueous dispersion was adjusted to 10 with triethylamine, and 150 mg of EPOSS was added and stirred at room temperature for 24 hours to obtain an active spray solution, referred to as AS15.
[0049] The preparation method of CPB is the same as that of Comparative Example 1, except that SH:butadiene=1:1, the amount of DMPA used is 25 mg (1 wt%), the illumination time is 10 min, and the carboxyl grafting rate is 60%, referred to as CPB60.
[0050] The spraying method is the same as that of Comparative Example 1, except that the spraying liquid is AS15 and the obtained material is CPB60-AS15.
[0051] Figure 3 The electron microscope photos of the surfaces of Comparative Example 1 (a) and Example 3 (b) after being treated with sandpaper show that Example 3 has fewer surface scratches and better abrasion resistance.
[0052] Comparative Example 2
[0053] Under constant nitrogen conditions, 0.54g of 1,2-PB with a number average molecular weight of 1000 and a 1,2-structure content of 70% was dissolved in 20mL of tetrahydrofuran, 0.7mL (SH: butadiene = 1:1) 2-mercaptoethanol was added to the solution and stirred evenly, and then 25mg (1wt%) of photoinitiator dimethyl benzoate (DMPA) was dissolved in 1mL of tetrahydrofuran and added to the solution. The reaction was placed under a 365nm ultraviolet lamp for 4 minutes. After the reaction was completed, 1mL of ethanol containing 1wt% 264-antiaging agent was added to the system to terminate the reaction. The product was poured into a mold and dried to obtain 1,2-polybutadiene with a hydroxyl grafting rate of 70%, referred to as HPB70.
[0054] After HPB70 was coated on the surface of styrene butadiene rubber and dried, T5 was sprayed on the surface of HPB using a spray gun under a pre-stretching state of 100%, and both sides were sprayed. The material was heated at 160°C for 40 minutes to obtain a polymer material with a conductive coating, referred to as HPB70-T5.
[0055] Example 4
[0056] After HPB70 was coated on the surface of styrene-butadiene rubber and dried, AS5 was sprayed on the surface of HPB70 using a spray gun under a 100% pre-stretching state, with both sides sprayed, and heated at 160°C for 40 minutes to obtain a polymer material with a conductive coating, referred to as HPB70-AS5.
[0057] Figure 4The resistance changes of comparative example 2 and example 4 after 1000 bending fatigues are shown. The resistance of comparative example 2 increases rapidly after bending, while the resistance of example 4 is relatively stable, with a smaller rate of change and better fatigue resistance.
[0058] Example 5
[0059] Under constant nitrogen conditions, 0.54g of 1,2-PB with a number average molecular weight of 150,000 and a 1,2-structure content of 95% was dissolved in 20mL of tetrahydrofuran, 0.8mL (SH: butadiene = 1:1) mercaptoethylamine was added to the solution and stirred evenly, and then 25mg (1wt%) of photoinitiator dimethyl benzoate (DMPA) was dissolved in 1mL of tetrahydrofuran and added to the solution. Place it under a 365nm ultraviolet lamp for 4min of light reaction. After the reaction is completed, 1mL of ethanol containing 1wt% 264-antiaging agent is added to the system to terminate the reaction. The product was poured into a mold and dried to obtain 1,2-polybutadiene with an amino grafting rate of 70%, referred to as NPB70.
[0060] When NPB70 is pre-stretched 100%, AS5 is sprayed onto the surface of NPB using a spray gun, both sides are sprayed, and the material is heated at 140° C. for 20 minutes to obtain a polymer material with a conductive coating, referred to as NPB70-AS5.
[0061] The flame retardant properties of the samples of the above embodiments and comparative examples were tested, and the test results are shown in Table 1.
[0062] Table 1 Flame retardant properties of samples
[0063]
[0064] As shown in Table 1, the active-stretch spraying strategy adopted in the present invention can prepare electromagnetic shielding materials with an electromagnetic shielding efficiency higher than 20 dB, and the preparation method is simple, the sprayed coating thickness is only 2 μm, and only 3 to 5 g MXene per square meter is required. A small amount of spraying liquid can prepare electromagnetic shielding materials for commercial use, which can achieve large-scale preparation. 3 C 2 T x Nanosheet CPB has a higher smoke production rate and is sprayed with Ti 3 C 2 T x The smoke production is significantly reduced after the nanosheets are added, because Ti 3 C 2 T x The tortuous path of the nanosheet layer of the nanosheet suppresses the generation of smoke. 3 C 2 T x / EPOSS active spray liquid, the cage-shaped Si-O structure of EPOSS isolates oxygen, while ensuring low smoke generation, the ignition time is extended, the burning time is shortened, and the flame retardant performance is further improved.
[0065] In addition, the substrate used in the present invention is 1,2-PB modified by click chemistry. A large number of polar groups usually make it have good adhesion to metal materials, and 1,2-PB contains residual double bonds that can further react. Therefore, it can be coated on a variety of materials that need to shield electromagnetic waves, and has broad application prospects.
Claims
1. A method for preparing a flame retardant high-performance electromagnetic shielding material, characterized in that: Using single / multi-layer Ti3C2T x The dispersion formed by self-assembly of an aqueous solution of type MXene nanosheets and epoxy cage silsesquioxane is the spraying liquid, the mass ratio of MXene nanosheets to epoxy cage silsesquioxane is 100:5-15, and it is sprayed onto a pre-stretched functionalized 1,2-polybutadiene polymer substrate, the functionalized polymer substrate is 1,2-polybutadiene functionalized with hydroxyl, carboxyl or amino, and the grafting rate is 40-70%, and an electromagnetic shielding film is formed under heating conditions.
2. The method for preparing a flame retardant high-performance electromagnetic shielding material according to claim 1, characterized in that: The pH of the aqueous solution of MXene nanosheets was adjusted to 8-10 by triethylamine.
3. The method for preparing a flame retardant high-performance electromagnetic shielding material according to claim 1, characterized in that: The dispersion formed by the self-assembly of the aqueous solution of MXene nanosheets and epoxy cage-shaped silsesquioxane is prepared by dissolving the epoxy cage-shaped silsesquioxane in a polar organic solvent and then adding the dissolved epoxy cage-shaped silsesquioxane into the aqueous solution of MXene nanosheets and mixing them evenly by stirring or ultrasonic treatment; the polar organic solvent is tetrahydrofuran.
4. The method for preparing a flame retardant high-performance electromagnetic shielding material according to claim 1, characterized in that: The hydroxyl, carboxyl or amino functionalized 1,2-polybutadiene is prepared by a click chemistry method using 1,2-polybutadiene and a thiol containing a hydroxyl, carboxyl or amino group. The preparation steps include: dissolving the 1,2-polybutadiene rubber in a polar organic solvent, adding the thiol, adding a photoinitiator, and initiating the reaction with ultraviolet light at room temperature for 4 to 10 minutes; the amount of the photoinitiator used is 0.4 to 1% of the mass of the 1,2-polybutadiene rubber.
5. The method for preparing a flame retardant high-performance electromagnetic shielding material according to claim 1, characterized in that: The thiol containing hydroxyl, carboxyl or amino group is at least one of 3-mercaptopropionic acid, 2-mercaptoethanol, mercaptoethylamine and cysteine, and the added amount is 0.2 to 1:1, calculated by the molar ratio of thiol:butadiene.
6. The method for preparing a flame retardant high-performance electromagnetic shielding material according to claim 1, characterized in that: The number average molecular weight of 1,2-polybutadiene is 1000 to 150,000, and the 1,2-structure content is 75 to 95%.
7. The method for preparing a flame retardant high-performance electromagnetic shielding material according to claim 1, characterized in that: The heating conditions are heating at 140-160°C for 20-40 minutes.
8. A flame retardant high-performance electromagnetic shielding material, characterized in that: The method is prepared by any one of claims 1 to 7.
Citation Information
Patent Citations
Separated imperata cylindrica polysaccharide and application thereof
CN110117331A
Preparation method of isolated thermoplastic elastomer composite microporous electromagnetic shielding material
CN111592684A